2022
DOI: 10.1097/md.0000000000032017
|View full text |Cite
|
Sign up to set email alerts
|

Association between various breathing indexes during sleep and the Epworth Sleepiness Scale score in adults

Abstract: Some breathing indexes during sleep, including the apnea-hypopnea index, oxygen desaturation index, and oxygen saturation during sleep, can be recorded by overnight polysomnography. We aimed to investigate the association of various breathing indexes during sleep with the Epworth Sleepiness Scale (ESS) score in adults. We retrospectively collected the clinical and overnight polysomnography data of 2829 adults aged 20 years or older from November 2011 to June 2017. The association of various breathing indexes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In addition, Nguyen et al constructed a Bland–Altman plot showing the mean ESS scores against the difference in the two scores and it suggested low test–retest reliability of ESS specifically in a population being investigated for OSA. A similar study was conducted by Taylor et al but, rather than 2, they tracked 3 different Epworth scores per person from general practitioner ESS, overnight oximetry ESS, and sleep specialist ESS and they observed a poor test–retest as well ( 52 ), further supporting the conclusions drawn by Nguyen et al Another study observed low test–retest reliability even when the ESS test is repeatedly administered on the same day ( 53 ).…”
Section: Discussionsupporting
confidence: 57%
“…In addition, Nguyen et al constructed a Bland–Altman plot showing the mean ESS scores against the difference in the two scores and it suggested low test–retest reliability of ESS specifically in a population being investigated for OSA. A similar study was conducted by Taylor et al but, rather than 2, they tracked 3 different Epworth scores per person from general practitioner ESS, overnight oximetry ESS, and sleep specialist ESS and they observed a poor test–retest as well ( 52 ), further supporting the conclusions drawn by Nguyen et al Another study observed low test–retest reliability even when the ESS test is repeatedly administered on the same day ( 53 ).…”
Section: Discussionsupporting
confidence: 57%